Microbial Contamination of the Outer Surface of X-ray Films - Farhadi, Elham; Niknami, Mahdi; Hakemivala, Mojdeh; Gandomi, Shiva (Journal of Dental School, 2021)
Objectives Infection control is one of the most important aspects of dentistry. Since intraoral radiographic films are directly in contact with the oral environment, microbial contamination may transmit infectious diseases. The purpose of this study was to investigate the frequency of microbial contamination of intraoral radiographic films and compare the probable microbial contamination of two intraoral radiographic film brands available in the Iranian market. Methods in this in vitro, experimental study, 900 radiographic films of two commercial brands, i.e. Intra X-ray and Carestream films were placed in aerobic, anaerobic, and fungal culture media immediately after removal from the packaging in sterile conditions. The samples were transferred to the respective culture media after incubation. The cultured bacteria were Gram-stained, and microscopically observed. The percentage of the contaminated intraoral radiographic films and the type of microbial contamination were reported. Data were analyzed using the Chi-square test. Results Of all, 32.6% of the Carestream films and 44.6% of Intra X-ray films were infected by aerobic microorganisms, mostly Bacillus. In the anaerobic culture, the turbidity of the medium indicated the possible presence of microorganisms. In the fungal culture, no fungal hyphae were observed microscopically. Conclusion The results of this study showed that intraoral films cannot be considered sterile. Intra X-ray radiographic films were significantly more contaminated than Care stream radiographic films.